KOMUNIKASI PROMOSI BERSAMA DALAM MENINGKATKAN PENJUALAN PRODUK MASYARAKAT DESA DI KECAMATAN WARINGIN KURUNG - Restu Wahyuni; Rachmi Yulianti (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2017)
This study try to apply the promotion of communications collectively on the products of the village community with model pamphlet commerce and analyze the level of sales before and after promotion with model pamphlet commerce is applied. The results of this study are expected to minimally be able to overcome the impasse of marketing of village products that are less widespread and often trapped by the realtor marketing system. This research method using research development approach (R&D) of data in a limited, the research shows that the hypothesis testing on the application of pamphlet model commerce product of the village community as a joint promotion communication conducted in the sub-district waringinkurung generated t hitung of -2.463, which then the value is compared with the value of t table with degrees of freedom (dk) = n1 + n2 7 + 7 = 14 - 2 = 12. and the error rate of 5%, then t table (0.05) (12) = -2.178 and in accordance with the test criteria that have been determined the results of the comparative hypothesis post test) on the implementation of the trade pamphlet t is less than t table (-2,463 <-2,178) so that the meaning is there is a significant difference in the effectiveness of product sales performance of villagers in Waringin Kurung subdistrict before and after the application of commercial pamphlet model as a promotion communication with him.